Best Practices for Supporting Employees Through Times of Transition - Nuraini, Nuraini (YUME : Journal of Management, 2024)
This qualitative study delves into transition support interventions within organizational settings. The research aims to explore the significance of effective communication, social support networks, training and development programs, and organizational policies in facilitating successful transitions. Using a systematic review and thematic analysis approach, the study synthesizes existing literature from scholarly articles and academic publications. Findings underscore the pivotal role of clear, two-way communication channels, peer support groups, mentorship programs, immersive learning experiences, flexible work arrangements, and employee assistance programs in supporting employees through transitions. The research highlights the importance of fostering a culture of trust, openness, and inclusivity within organizations to promote employee resilience and well-being during times of change. Key insights include the transformative impact of digital technologies on organizational communication and the need for comprehensive frameworks to assess the effectiveness of transition support interventions. Overall, the study contributes to a deeper understanding of evidence-based practices for promoting employee well-being, organizational effectiveness, and sustainability amidst transition and uncertainty. Keyword: Communication; Social Support; Training and Development; Organizational Policies; Transition Support.